2007
DOI: 10.3201/eid1310.070158
|View full text |Cite
|
Sign up to set email alerts
|

Novel Variant of Tickborne Encephalitis Virus, Russia

Abstract: We isolated a novel strain of tickborne encephalitis virus (TBEV), Glubinnoe/2004, from a patient with a fatal case in Russia. We sequenced the strain, whose landmark features included 57 amino acid substitutions and 5 modified cleavage sites. Phylogenetically, Glubinnoe/2004 is a novel variant that belongs to the Eastern type of TBEV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 8 publications
1
5
0
2
Order By: Relevance
“…These results confirm the results of the authors' previous studies (20,26) as well as other studies that showed replication of highly virulent strains of TBEV starting from 12 h pi by using different cell cultures (31,35,45,52).…”
Section: Dynamics Of Infection Of Donors' Blood Cells By Tbev Strainssupporting
confidence: 95%
“…These results confirm the results of the authors' previous studies (20,26) as well as other studies that showed replication of highly virulent strains of TBEV starting from 12 h pi by using different cell cultures (31,35,45,52).…”
Section: Dynamics Of Infection Of Donors' Blood Cells By Tbev Strainssupporting
confidence: 95%
“…However, to investigate more detailed and improved phylogeny of TBEV, a complete genome-based phylogenetic analysis is indispensable. Here, we performed a larger phylogenetic analysis than a previous study [37], using 31 fully sequenced TBEV strains and two complete polyprotein sequences. The complete genome-based phylogenetic tree showed that viruses were obviously divided three distinct subtypes and revealed that the two TBEV Korean strains are more closely related to the Salem and Czech 263 strains of the Western subtype than to other TBEV strains.…”
Section: Discussionmentioning
confidence: 99%
“…TBEV antigens were detected via enzyme immunoassay analysis as described previously (Ternovoi et al 2007). Briefly, the viral antigen was captured on the surface of 96-well polystyrene plates from 100 µl of the homogenates of ticks and internal organs (spleen, liver and brain from individual bird) using monoclonal antibodies 10H10 against protein E of TBEV that was preliminarily immobilised on the plates.…”
Section: Enzyme Immunoassaymentioning
confidence: 99%